BUILDING PROSPECTIVE SCHOOL MATHEMATICS UNDERSTANDING OF PROSPECTIVE TEACHERS THROUGH ALGEBRA ABSTRACT COURSE - Melda Jaya Saragih; Tanti Listiani (Universitas Negeri Makassar, 2023)
Prospective math teacher students are prepared to become math teachers where they will teach school mathematics, but students need to be equipped with pure mathematics such as abstract algebra which is the foundation of mathematics itself and not only given school mathematics knowledge, so students can learn to form a solid understanding of mathematics . The structure of mathematics, including abstract algebra, is generally consistent, logical, systematic, making everyone who studies it requires complex abilities, so it often makes people who study it experience difficulties and feel unrelated to their preparation for teaching school mathematics. The purpose of this research is to find out how students as prospective teachers develop their understanding of the relationship between Abstract Algebra courses and mathematics taught in schools through each essential question and project in the form of abstract algebra applications in everyday life, school mathematics and other fields after attending Algebra lectures. abstract. The method used in this study is a quantitative method with a pretest-posttest group design using the Wilcoxon non-parametric test. Data collection through questionnaires, and student interviews. The results of the study show that through a series of abstract algebra lectures students realize that abstract algebra courses are the foundation for teaching school mathematics because the use of abstract algebra material is closely related to everyday life, school mathematics and other fields.